Design and Implementation of a Low-Cost and Functional Prosthetic Hand Using 3D Printing Technology for a Member of the Association of Physical Disabilities Indonesia - Triwiyanto, Triwiyanto; Luthfiyah, Sari; Forra Wakidi, Levana; Utomo, Bedjo (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
Many people with physical disabilities, especially transradial amputees, face difficulties in performing daily activities and have low self-esteem due to the lack of affordable and functional prosthetic hands. The aim of this community service program is to apply 3D printing technology in making prosthetic hands for the members of the Indonesian Physical Disability Association (PPDFI) branch in Surabaya. The method consists of four steps: (1) measuring the physical parameters of the amputees, such as the circumference and length of the residual limb, (2) designing and printing the prosthetic hand using 3D software and printer, (3) testing the mechanical and functional performance of the prosthetic hand, such as the ability to open and close, and (4) providing counseling and mentoring to the amputees to restore their confidence and evaluate their usage. Result: The result of this program is the availability of a low-cost and open-source prosthetic hand for the transradial amputees, which can help them to perform basic activities such as driving, holding a phone, and grabbing a bottle. The prosthetic hand can also be customized according to the needs and preferences of the amputees, such as the color or design. Conclusion: The conclusion of this program is that 3D printing technology can be used to create a functional and affordable prosthetic hand for the transradial amputees, which can improve their quality of life and self-esteem. The program also provides education and guidance to the amputees and the community about the benefits and risks of using prosthetic hands.